PENGARUH PERILAKU KEPEMIMPINAN, DISIPLIN KERJA DAN PENGAWASAN INTERNAL TERHADAP KINERJA ANGGOTA POLRI SATUAN SABHARA POLRES MUNA - Adri Pontjodiredjo; Ibnu Hajar; Muhammad Masri; Agustinus Tangalayuk (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
This study aims to: 1) determine the influence of leadership behavior, work discipline, and internal control simultaneously on the performance of the Sabhara unit of the Muna Police, 2) to determine the effect of leadership behavior on the performance of the personnel of the Sabhara Police of Muna, 3) to determine the effect of work discipline on the performance of the personnel. the Sabhara unit of the Muna Police, and 4) knowing the effect of internal control on the performance of the personnel of the Sabhara unit of the Muna Police.The object of this research is the personnel of the Sabhara unit of the Muna Police. The population of the study was the police officers who served in the Sabhara unit of the Muna Police with a total of 65 personnel. Collecting research data using questionnaires, research data were analyzed using SPSS ver 22 to determine the results of regression analysis of the influence of the independent variable on the dependent variable.The results of the study: 1) Leadership behavior has a positive and significant effect on the performance of the members of the Sabhara Polres Muna Police Unit, 2) Work discipline partially has a positive and significant effect on the performance of the members of the National Police Unit Unit Sabhara Polres Muna, 3) Partial internal supervision has a positive effect and significant on the performance of the members of the Sabhara Police Unit of the Muna Police, and 4) The simultaneous and positive influence of leadership behavior, work discipline, and internal control on the performance of the members of the Sabhara Police of the Muna Police.